Conservative management of calcaneal fractures. a retrospective review of treatment outcome. - Wong, H.Y.; Vivek, A.S.; To, B.C.S. (2008)
Int roduction: Treatment of calcaneal fracture is still controversial and indication for surgery is not well established. We are reporting the mid term outcome of calcanel fractures treated conservatively. Material and Methods: Patients admitted with calcaneal fractures from 1st November 2002 till 31st December 2004 and were treated conservatively were included in this study. The fractures were grouped according to Essex-Lopresti classification and their outcomes were assessed with the Maryland foot score. We also looked at time to weight bearing and returning to occupational activity. Results: Forty-four patients were included for evaluation. Patients with extraarticular calcaneal fractures had significantly higher rating scores compared to those with intraarticular fractures (98.2 and 88.8 respectively, with a p value = 0.0001). Generally, both group of patients had a good clinical outcome. 18 of the 44 patients (41) started partial weight bearing before or at 6 weeks and 31 patients (72) were able to start full weight bearing by 12 weeks. 31 patients (72) were back to work 12 weeks after the injury. Conclusion: Conservative management for calcaneal fractures is an acceptable mode of treatment with satisfactoryfunctional outcome.